Implementation of Industrial Revolution 4.0 in construction projects / Nicole Wee Zhen Zhi ... [et al.] - Wee Zhen Zhi, Nicole; Wai Wah, Low; Shi Yee, Wong; Kwong Soon, Wong (2021)
The world is moving toward digitalization era. In view of this, government from different regions are endeavour to embark on this shift by integrating digitalization strategies in the policy making. However, the implication of implementing Industrial Revolution 4.0 (IR 4.0) in construction projects is not fully explored. As such, the objectives of this study were to identify the critical barriers and impacts of the implementation of IR 4.0 in construction projects. In view of time and funding constraints, this study was limited in the Malaysia region. Questionnaire was designed to gauge the opinions of construction stakeholders on the implementation of IR 4.0 in construction projects. It was found that the most critical barriers were 'additional time is required', 'lack of technical and knowledgeable staff, 'lack of financial resources' and 'lack of manpower'. The critical positive impact of IR 4.0 implementation in construction projects were 'safety', 'project success' and 'time performance'. This study provides information to the relevant stakeholders to propose more practical strategies to assist construction stakeholders to embark on IR 4.0 in construction projects.